The impact of cultural intelligence on negotiation outcome - Harn Jean, Goh (2014)
Globalization increases human interaction across boundaries. It expose people of different shared values and norms to interact with each other. Project managers play a prominent role in interacting and negotiating with people of different culture, background and belief. Ability of individuals to negotiate effectively across culture improve relationship and organizational performance. Cultural intelligence, a newly introduced term to the business world, is said to be a key to success in negotiation domain. Studies claimed that cultural intelligence is implemented during cross cultural interaction, but there is limited research of cultural intelligence on negotiation domain. Thus, this study aim to identify whether cultural intelligence is a factor in negotiation outcome. Secondly, to determine the component of cultural intelligence that has the highest influence on negotiation outcome. Data were collected using questionnaires where target respondents are project managers of Grade 7 construction companies, situated in Pahang area. Result revealed that cultural intelligence is a factor in negotiation outcome and motivational cultural intelligence have the highest influence on negotiation outcome. The influential level of every components are not distinctively different, thus it can be said that each component are equally important to each component in achieving a higher cultural intelligence. Corporate and business world should start taking consideration of nurturing cultural intelligence among employees